2006
DOI: 10.1210/jc.2005-2537
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin Receptor Epitopes and Their Relation to Histocompatibility Leukocyte Antigen-DR Molecules in Graves’ Disease

Abstract: Three different methods for identifying immunogenic peptides did not provide a uniform picture of important TSHR epitopes. However, peptide 132-150 (GIFNTGLKMFPDLTKVYST) was identified by three methods as an important epitope in GD; the possible importance of peptides 145-163, 158-176, 207-222, 248-263, 272-291, and 343-362 was also identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…In a recent study we reported the IC50 values for TSH-R-ECD synthetic peptide epitopes binding to several purified HLA molecules, including DR3 (18). We found that peptides 8, 10, and 13, bearing sequences IRNTRNLTYIDPDALKE (109-124), GIFNTGLKMFPDLTKVYST (132-150), and GLKMFPDLTKVYST (137-150) of TSH-R-ECD, bound with very high affinity to HLA-DR-3.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a recent study we reported the IC50 values for TSH-R-ECD synthetic peptide epitopes binding to several purified HLA molecules, including DR3 (18). We found that peptides 8, 10, and 13, bearing sequences IRNTRNLTYIDPDALKE (109-124), GIFNTGLKMFPDLTKVYST (132-150), and GLKMFPDLTKVYST (137-150) of TSH-R-ECD, bound with very high affinity to HLA-DR-3.…”
Section: Discussionmentioning
confidence: 95%
“…We also compared responses of T cell immunized in vivo to recent published studies describing in vitro TSH-R-ECD peptide binding to HLA-DR molecules (18).…”
mentioning
confidence: 99%
“…The common ground between these tools is the ability to quickly screen large datasets, including whole genomes, for prediction of T cell epitopes. These types of predictions have successfully been applied both to vaccine development [37][38][39][40][41] and to the identification of key epitopes triggering autoimmunity [42].…”
Section: In Silico Analysis Toolsmentioning
confidence: 99%
“…Thirty-one 16-20 mer peptides covering the entire sequence of TSH-R-ECD with overlaps of five to six amino acids were synthesized as reported (16,17). In addition, 10 TSH-R-ECD peptides, listed as peptide 32-41, were newly synthesized, These peptides were predicted by EpiMatrix (18) to have high binding affinity for HLA-DR3 (peptides 32-36) or multiple DRs (peptides 37-41).…”
Section: Tsh-r-ecd Peptides and Competing Peptidesmentioning
confidence: 99%